Rancang Bangun Alat Pengatur Suhu Kandang Bayi Burung Murai Batu dengan Menggunakan Metode Fuzzy Logic Berbasis Arduino - Suryadi, Angga; Muiz, Adam; Habibie, Muhammad Alwi (Dinasti Research, 2025)
Murai Batu is a bird species that has a high selling value and is popular in Indonesia. Because the demand for magpie chicks is quite high, many breeders harvest magpie chicks when they are still babies so that the parents can produce again. However, many magpie magpie birds are still cultivated manually, both in the process of controlling environmental conditions around the cage and in the process of breeding baby birds. One of the problems that often occurs is unstable temperature and humidity in baby birds, where baby rock magpie birds aged 0-5 days can survive at an ideal temperature in the range of 25℃-35℃ and ideal humidity between 60% - 80% . Therefore, to maintain temperature and humidity conditions, a system was designed that can control the temperature and humidity in the baby magpie batu bird's cage. This system applies a fuzzy logic method which is used to control the lights and fans to turn on automatically when the cage temperature is outside the ideal temperature for magpie chicks. Components used include Arduino Uno, DHT11 sensor, relays, fans and lights. The results of this research have resulted in the realization of a temperature and humidity control system in the Murai Batu baby bird cage using fuzzy logic with a set setpoint. Output testing (fan and lights) was carried out on the tool to obtain results that were in accordance with what was expected. With the presence of a temperature control device for baby magpie batu birds, it is hoped that it can increase the success rate in rearing baby magpie batu.